Designing embedded systems and the internet of things (IoT) with the ARM Mbed - Xiao, Perry (John Wiley & Sons, Inc., 2018)
Designing Embedded Systems and the Internet of Things (IoT) with the ARM Mbed offers an accessible guide to the development of ARM Mbed and includes a range of topics on the subject from the basic to the advanced. ARM Mbed is a platform and operating system based on 32-bit ARM Cortex-M microcontrollers. This important resource puts the focus on ARM Mbed NXP LPC1768 and FRDM-K64F evaluation boards. NXP LPC1768 has powerful features such as a fast microcontroller, various digital and analog I/Os, various serial communication interfaces and a very easy to use Web based compiler. It is one of the most popular kits that are used to study and create projects. FRDM-K64F is relatively new and largely compatible with NXP LPC1768 but with even more powerful features--